Antibody to poly(adenosine diphosphate-ribose) polymerase and its use in chromatin analysis. - Malik, N (1982)
To facilitate investigations on the organization of poly (ADP-Rib) polymerase in chromatin, and to elucidate its biological function, polymerase purified from HeLa nuclei was used to elicit antibodies in mice. The anti-polymerase sera was found to be specific by multiple criteria. The association of polymerase with oligonucleosomes of differing chain size was determined by the specific binding of polymerase antibody (and as control, anti-histone H3) to nitrocellulose transfers of native electrophoretic gels of these particles. By this technique, polymerase appears to be associated with a select subclass of nucleosomes. Further resolution of the polymerase binding sites within nucleosome classes was achieved with the antibody by two-dimensional native polyacrylamide gel electrophoresis and nitrocellulose transfer.